Analysis Of Derivative Suits As A Form Of Legal Protection For Foreign Investors In Investment Activities In Indonesia - Permatanta, Sry Enda (LPPM Universitas PGRI Sumatera Barat, 2024)
Investment is an important area that makes a major contribution to the country's economic growth. Law Number 11 of 2020 concerning Job Creation changes the provisions regarding capital investment which were previously regulated in Law Number 25 of 2007 concerning Capital Investment. The research in this article uses a normative legal research method. In this study, researchers examine and detail a problem using secondary data to find a solution. The process of collecting data to solve the problem is carried out through library research, which is then analyzed qualitatively. These changes include the elimination of business sectors that are prohibited from investing, from 20 business sectors to only 6 business sectors. This change is expected to expand the investment space in Indonesia and bring progress in the economic and technological fields. In response to these challenges, the Indonesian government has introduced the Job Creation Law. This law is designed with the main objective of creating jobs through simplification, protection, and empowerment for cooperatives, MSMEs, and national industry and trade. This step aims to create jobs in Indonesia efficiently, while paying attention to the balance and development between regions in the context of the national economy.